Developing Mission Model Canvas for Mission-Driven Organization: Case Study Scholarship Program of Indonesia Endowment Fund for Education - Mochammad Thanthowy Syamsuddin (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2022)
Indonesia Endowment Fund for Education is a Public Service Organization under the Indonesia Ministry of Finance designed to provide scholarship and research funding for Indonesian citizens. At that time, they have not developed a model canvas while at the same time organization facing more opportunities and challenges in education and talent agencies in the country. The study uses a model canvas framework with a qualitative methodology. The study defines business issues through observation first, followed by a literature review related to the problem. The data analysis of semi-structured interviews and benchmarking with other scholarship providers was conducted to address the issue. This research found that the pre-development of the model canvas of the organization is underdeveloped; thus, the new mission model canvas is proposed to answer future opportunities and challenges.